Cholesterol metabolism dysregulation in eyelid sebaceous gland carcinoma and its clinical significance - Sahar Rafat; Seema Sen; Kunzang Chosdol; Sameer Bakhshi; Seema Kashyap; Neelam Pushker (Indian Journal of Ophthalmology, 2026)
Purpose: Eyelid sebaceous gland carcinoma (SGC) is a rare and aggressive malignancy of the eyelids. Dysregulated cholesterol metabolism has been found to be involved in pathogenesis of various cancers including glioblastoma, breast, prostate, and pancreatic cancer. The role of cholesterol metabolism in SGC and its molecular characterization remains unexplored. This study evaluates the clinical significance of the expression of a key enzyme involved in cholesterol metabolism, acyl-CoA cholesterol acyltransferase 1 (ACAT1) in eyelid SGC. Methods: A cohort of 50 eyelid SGC cases diagnosed over a period of 12 years were selected. Cholesterol quantification, immunohistochemistry (IHC), and real-time PCR to determine the protein and mRNA expression of ACAT were performed. Results: Increased concentration of total cholesterol, free cholesterol, and cholesteryl esters was observed in SGC tumor tissues. Overexpression of ACAT1 at protein and mRNA levels was observed in 66% of the eyelid SGC patients. Significant association of high ACAT1 mRNA expression was observed in patients with lymph node metastasis ( P = 0.03) and advanced (III/IV) tumor stage ( P = 0.02). SGC patients with a high ACAT immunoexpression also had reduced disease-free survival. Conclusion: Overexpression of ACAT1 is a frequent event in the pathogenesis of eyelid SGC and is associated with high risk clinicopathological features. It could serve as a reliable poor prognostic biomarker.